Management of anterior cruciate ligament tears in skeletally immature athletes. Issue 4 (2nd October 2015) - Ludwig, Meryl; Atanda, Alfred
Abstract: The prevalence of anterior cruciate ligament (ACL) injuries in skeletally immature athletes has increased dramatically over the past decade. Many attribute this to increased training, single-sport specialization and year-round competitive play. ACL injuries most commonly occur in athletic activities that involve cutting, pivoting, jumping and landing. Non-operative treatment consisting of activity modification, physical therapy and specialized bracing may have a role; however, recent data suggest that this may not be optimal in young, active patients. Surgical treatment has become more favorable, specifically for athletes with aspirations of higher-level sports participation. To minimize growth plate disturbances and potential for limb malalignment, the patient's skeletal age, pubertal status and remaining growth potential must be taken into consideration. We provide a review on how to evaluate, manage and treat the skeletally immature athlete with an ACL injury.